CARDIOVASCULAR RISK FACTORS AMONG NEWLY DIAGNOSED PROSTATE CANCER PATIENTS - Warman, Putri Liana; Pramod, Sawkar Vijay (Indonesian Journal of Urology, 2026)
Introduction: Patients with prostate cancer (PCa) are less likely to die of prostate cancer than of non-prostate causes such as cardiovascular disease (CVD). Recently, Jakarta Cardiovascular Risk score prediction models were developed and validated with good reliability in predicting 10-year cardiovascular events in the Indonesian population. Objective: This study aims to describe cardiovascular risk factors among newly diagnosed prostate cancer patients. Material & Methods: This is a cross-sectional, retrospective study of patients with newly diagnosed prostate cancer at Hasan Sadikin Academic Medical Center from 2013 to 2023. The Jakarta CV Risk score was calculated on all populations and among groups according to tumor extension: local (T1-T2), locally advanced (T3-T4), and metastatic. A score of -7 to 1 was considered a low risk for CV event, 2 – 4 was intermediate risk, and >4 was considered high-risk. Results: There were a total of 118 subjects included in this study. The mean age was 67.5 ± 9.7 years, the mean BMI was 22.3 ± 2.79 kg/m2. The average Jakarta cardiovascular score in this population was 7.25 ± 2.24. In the local PCa group (T1-T2) was 6.97 ±1.99 (high risk); in the locally advanced PCa group (T3-T4) was 7.30 ± 1.70 (high risk); and in the metastatic group was 7.14 ± 2.08 (high risk). Unfortunately, there are 22 (19.5%) patients who will be planned to receive Androgen-deprivation therapy based on staging. Conclusion: Patients with newly diagnosed PCa commonly have high cardiovascular risk and it should be our consideration for giving ADT treatment. Keywords: Prostate cancer, cardiovascular disease, Jakarta cardiovascular risk score, androgen-deprivation therapy.